Clinical pharmacoepidemiology of antibiotics usage in intensive care unit of cancer special hospital - Akrom Akrom; Rafiastiana Capritasari (International Journal of Public Health Science (IJPHS), 2020)
The pattern of antibiotics use in cancer patients in the intensive care unit (ICU) of dharma is cancer special hospital (DCSH) has not been identified. The purpose of this study is to determine the pattern of antibiotics use in cancer patients treated in the ICU of DCSH from 2012-2014. This study was observational with a cross-sectional design. The data collection is done retrospectively. The inclusion criteria to recruit the subjects, i.e. Adult patients who had nosocomial infections in the ICU; Patients with medical records in the ICU who received antibiotics in the 2012-2014 periods. Patients originating from inpatients (wards); Patients with medical records were read. The exclusion criteria were postoperative patients and Patients with incomplete medical records. We collected data from medical records of cancer patients who had been admitted to the ICU in 2012-2014, medication administration records, sample submission, and laboratory records. There are 202 cancer patients including in the study. Leukemia and breast cancer were the most cancer’s diagnosis in the Subject. More than two hundred cancer patients were receiving antibiotic therapy, with more than 50% of them were diagnosed with pneumonia, followed by central infection (>20%) and urinary tract infection (>10%). The antibiotic most frequently used was meropenem, with 33.8%. The three most commonly used antibiotics from 2012 to 2014 were meropenem, levofloxacin, and ceftriaxone.